Resolved but not forgotten: Stroop conflict dredges up the past - Hazeltine, Eliot; Mordkoff, J. Toby (Frontiers in Psychology, 2014)
The magnitude of congruency effects depends on, among other things, the specifics of previously trials. To explain these modulating effects, a host of mechanisms by which previous trials affect the processing of relevant and irrelevant information on the present trial have been proposed, including feature-repetition advantages, negative priming, item-specific proportion congruency (ISPC) effects, display-frequency effects, and sequential modulations of both congruency and frequency effects. However, few experiments have been designed to independently manipulate these factors. In the present study, we used a four-choice Stroop task in which we hold constant the frequencies of the stimulus features and responses, but manipulate the frequencies of their conjunctions. We modified the procedure used by Jacoby et al. (2003), under which the possible word-color pairings differed in terms of proportion occurrence, by adding neutral trials to obtain independent estimates of these various potential effects. The results indicate that feature repetitions, display frequency, and sequential modulations of both congruency and frequency effects all affect response time. However, no evidence for an ISPC effect was obtained; the display frequency effect measured on the neutral trials accounted for all differences in the congruency effect, as proposed by Schmidt and Besner (2008). Sequential modulations of congruency effects were observed when the overall proportion of congruent trials was held to a chance level and marginal display frequency was also held constant.